2016
DOI: 10.1111/omi.12149
|View full text |Cite
|
Sign up to set email alerts
|

Heme acquisition mechanisms of Porphyromonas gingivalis – strategies used in a polymicrobial community in a heme‐limited host environment

Abstract: Summary Porphyromonas gingivalis, a main etiologic agent and key pathogen responsible for initiation and progression of chronic periodontitis requires heme as a source of iron and protoporphyrin IX for its survival and the ability to establish an infection. Porphyromonas gingivalis is able to accumulate a defensive cell‐surface heme‐containing pigment in the form of μ‐oxo bisheme. The main sources of heme for P. gingivalis in vivo are hemoproteins present in saliva, gingival crevicular fluid, and erythrocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
151
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(160 citation statements)
references
References 186 publications
4
151
0
5
Order By: Relevance
“…Likewise, we must also consider the possibility that regardless of potential interaction between the bacterial species themselves, the presence of these multiple species could impact the immune response of the host, particularly by polyclonal activation of the lymphoid system and induction of immunological dysregulation (Montes, Acosta‐Rodriguez, Merino, Bermejo, & Gruppi, ). Alternatively, expression of virulence factors such as proteases or leukotoxins by some organisms may alter the ecological adaptation and virulence potential of other organisms in the same niche (Castro et al., ; Lohinai et al., ; Smalley & Olczak, ). Although these interactions have the potential to be extremely complex and time‐consuming to study, it is likely that this broader systems approach to the complex pathobiology of DD holds potential for more fully understanding the mechanisms and roles that each of these organisms may play in the disease process.…”
Section: Pathogens Involvedmentioning
confidence: 99%
“…Likewise, we must also consider the possibility that regardless of potential interaction between the bacterial species themselves, the presence of these multiple species could impact the immune response of the host, particularly by polyclonal activation of the lymphoid system and induction of immunological dysregulation (Montes, Acosta‐Rodriguez, Merino, Bermejo, & Gruppi, ). Alternatively, expression of virulence factors such as proteases or leukotoxins by some organisms may alter the ecological adaptation and virulence potential of other organisms in the same niche (Castro et al., ; Lohinai et al., ; Smalley & Olczak, ). Although these interactions have the potential to be extremely complex and time‐consuming to study, it is likely that this broader systems approach to the complex pathobiology of DD holds potential for more fully understanding the mechanisms and roles that each of these organisms may play in the disease process.…”
Section: Pathogens Involvedmentioning
confidence: 99%
“…The main source of heme in the human host is hemoglobin and P. gingivalis obtains heme from it with the aid of R‐ and K‐gingipains, and hemophore‐like proteins such as HmuY and HusA . Although R‐gingipain mediates oxidation of oxyHb to metHb for further globin degradation by K‐gingipain and eventual heme extraction by HmuY, here we have shown that the metHb formed by the action of H 2 O 2 produced by S. gordonii represents another potential source from which Fe(III)heme might be gained without the reliance upon R‐gingipain protease at a time when there is insufficient R‐gingipain expression by P. gingivalis .…”
Section: Resultsmentioning
confidence: 70%
“…Hanioka et al showed that Hb in gingival tissue may be up to 80% O 2 ‐saturated and hence any Hb entering the gingival sulcus or periodontal pocket following tissue bleeding will initially be largely oxygenated. For heme‐requiring organisms like P. gingivalis to use heme in the form of oxyHb they must be reliant upon mechanisms that guarantee the efficient conversion of oxyHb into the metHb form, from which heme may be more easily extracted . In this context, we observed that Hb extracted from S. gordonii zones of α‐hemolysis typically contained > 90% in the metHb form after 16 hours of aerobic growth, demonstrating that the organism can facilitate large‐scale oxidation of oxyHb.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The asaccharolytic nature of P. gingivalis is facilitated by its proteolytic capacity, which is vital for nutrition. As part of its function, proteolytic enzymes play a role in the acquisition of heme, a required component for growth, survival and virulence in the polymicrobial community of the heme‐limited host environment (reviewed by Smalley and Olczak and available in the accompanying virtual issue). The authors reviewed data that suggested that P. gingivalis uses a novel heme acquisition mechanism from hemoglobin.…”
mentioning
confidence: 99%